Association of vascular endothelial growth factor B (VEGFВ) gene polymorphisms with intracranial aneurysms - R. I. Sultanova; R. I. Khusainova; E. R. Lebedeva; M. A. Yankina; D. V. Gilev; E. K. Khusnutdinova (Вавиловский журнал генетики и селекции, 2019)
Intracranial aneurysm (IA) is a complex disease resulting in subarachnoid hemorrhage (SAH) due to a rupture. The average worldwide prevalence of this disease is about 2–5 %, with 50 % of them ending in death or neurological disorders of varying severity, with a high probability of recurrence of hemorrhage during the frst half of the year after rupture. Subarachnoid hemorrhage is annually registered in at least 18 thousand people in Russia. Associations of polymorphic variants rs594942 and rs11603042 of the VEGFB gene in intracranial aneurysm development in the Volga-Ural region of the Russian Federation with the presence of the symptom complex of undiﬀerentiated connective tissue dysplasia (uDST) and arterial hypertension (AH) were investigated. The C* allele rs594942 and rs11603042 of the VEGFB gene is a marker of an increased risk of IA as a whole (p = 0.025; χ2 = 5.052; OR = 1.32) in women as a whole (p = 0.001; χ2 = 10.124; OR = 1.70) and in comorbid state with uDCT (p = 0.002; χ2 = 9.501; OR = 2.34) and AG (p = 0.006; χ2 = 7.385; OR = 2.109). We found that the genotype *C*C of locus rs594942 of the VEGFB gene is a marker of an increased risk of intracranial aneurysm in general (p = 0.017; χ2 = 5.702; OR = 1.49) and among women in general (p = 0.0005; χ2 = 12.078; OR = 2.25) and with the symptomatic complex uCTD (p = 0.007; χ2 = 7.173; OR = 2.67) and AH (p = 0.010; χ2 = 6.471; OR = 2.51). We have obtained new results on the role of polymorphic variants of the VEGFB gene in the formation of intracranial aneurysm, taking into account the presence of the symptom complex uDCT and AH among the residents of the Volga-Ural region of Russia. A burdened comorbid background and the presence of undiﬀerentiated connective tissue dysplasia and arterial hypertension can contribute to an increased risk of intracranial aneurysm, as evidenced by the results of our study.